Pre-Exposure With Extracellular Vesicles From Aspergillus fumigatus Attenuates Inflammatory Response and Enhances Fungal Clearance in a Murine Model Pulmonary Aspergillosis - Souza, Jéssica Amanda Marques; Gurgel, Isabella Luísa da Silva; Malacco, Nathália Luísa Sousa de Oliveira; Martins, Flávia Rayssa Braga; Queiroz-Junior, Celso Martins; Teixeira, Mauro Martins; Soriani, Frederico Marianetti (Frontiers in Cellular and Infection Microbiology, 2022)
Aspergillus fumigatus is a ubiquitous and saprophytic filamentous fungus and the main etiologic agent of aspergillosis. Infections caused by A. fumigatus culminate in a strong inflammatory response that can evolve into respiratory failure and may be lethal in immunocompromised individuals. In the last decades, it has been demonstrated that extracellular vesicles (EVs) elicit a notable biological response in immune cells. EVs carry a variety of biomolecules, therefore are considered potential antigen delivery vehicles. The role of EVs as a strategy for modulating an effective response against infections caused by A. fumigatus remains unexplored. Here we investigate the use of EVs derived from A. fumigatus as an immunization tool to induce a more robust immune response to A. fumigatus pulmonary infection. In order to investigate that, male C57BL/6 mice were immunized with two doses of EVs and infected with A. fumigatus. Pre-exposure of mice to EVs was able to induce the production of specific IgG serum for fungal antigens. Besides that, the immunization with EVs reduced the neutrophilic infiltrate into the alveoli, as well as the extravasation of total proteins and the production of proinflammatory mediators IL-1β, IL-6, and CXCL-1. In addition, immunization prevented extensive lung tissue damage and also improved phagocytosis and fungus clearance. Noteworthy, immunization with EVs, associated with subclinical doses of Amphotericin B (AmB) treatment, rescued 50% of mice infected with A. fumigatus from lethal fungal pneumonia. Therefore, the present study shows a new role for A. fumigatus EVs as host inflammatory response modulators, suggesting their use as immunizing agents.